First-in-human evaluation of 6-bromo-7-[11C]methylpurine, a PET tracer for assessing the function of multidrug resistance-associated proteins in different tissues. - Mairinger, Severin; Jackwerth, Matthias; Chalampalakis, Zacharias; Rausch, Ivo; Weber, Maria; Wölfl-Duchek, Michael; Pracher, Lena; Nics, Lukas; Pahnke, Jens; Langsteger, Werner; Hacker, Marcus; Zeitlinger, Markus; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2024)
Purpose: Multidrug resistance-associated protein 1 (MRP1) is a transport protein with a widespread tissue distribution, which has been implicated in the pathophysiology of Alzheimer's and chronic respiratory disease. PET with 6-bromo-7-[11C]methylpurine ([11C]BMP) has been used to measure MRP1 function in rodents. In this study, [11C]BMP was for the first time characterised in humans to assess the function of MRP1 and other MRP subtypes in different tissues. Methods: Thirteen healthy volunteers (7 men, 6 women) underwent dynamic whole-body PET scans on a long axial field-of-view (LAFOV) PET/CT system after intravenous injection of [11C]BMP. Three subjects of each sex were scanned a second time to assess reproducibility. Volumes of interest were outlined for MRP-expressing tissues (cerebral cortex, cerebellum, choroid plexus, retina, lungs, myocardium, kidneys, and liver). From the time-activity curves, the elimination rate constant (kE, h− 1) was derived as a parameter for tissue MRP function and its test-retest variability (TRTV, %) was calculated. Radiation dosimetry was calculated using the Medical Internal Radiation Dose (MIRD) methodology. Results: Mean kE and corresponding TRTV values were: cerebral cortex: 0.055 ± 0.010 h− 1 (− 4 ± 24%), cerebellum: 0.033 ± 0.009 h− 1 (1 ± 39%), choroid plexus: 0.292 ± 0.059 h− 1 (0.1 ± 16%), retina: 0.234 ± 0.045 h− 1 (30 ± 38%), lungs: 0.875 ± 0.095 h− 1 (− 3 ± 11%), myocardium: 0.641 ± 0.105 h− 1 (11 ± 25%), kidneys: 1.378 ± 0.266 h− 1 (14 ± 16%), and liver: 0.685 ± 0.072 h− 1 (7 ± 9%). Significant sex differences were found for kE in the cerebellum, lungs and kidneys. Effective dose was 4.67 ± 0.18 µSv/MBq for men and 4.55 ± 0.18 µSv/MBq for women. Conclusion: LAFOV PET/CT with [11C]BMP potentially allows for simultaneous assessment of MRP function in multiple human tissues. Mean TRTV of kE in different tissues was in an acceptable range, except for the retina. The radiation dosimetry of [11C]BMP was in the typical range of 11C-tracers. LAFOV PET/CT holds great potential to assess at a whole-body, multi-tissue level molecular targets relevant for drug disposition in humans. Trial registration: EudraCT 2021-006348-29. Registered 15 December 2021.